A Comparative Study of Routing Protocols and Artificial Intelligence in Manets - Dolly Thakre; Poonam Sinha (International Journal of Mechanical Dynamics and Systems Analysis, 2024)
Decentralized networks called Mobile Ad hoc Networks (MANETs) allow mobile nodes to dynamically connect to one another without the need for fixed infrastructure. An overview of MANETs is given in this work, along with a discussion of their features, uses, and difficulties. It explores how routing protocols, such as proactive, reactive, and hybrid protocols, are categorized in MANETs and provides examples and features for each. It also examines the performance measures, including packet delivery ratio, throughput, packet loss, latency, routing overhead, energy consumption, and jitter that are used to assess routing protocols in MANETs. Furthermore, the study discusses how AI-driven systems enhance intrusion detection, reaction speed, and huge data management, emphasizing the significance of AI in improving security in MANETs.
Keywords: MANETs; Performance Metrics; Routing Protocols; artificial intelligence